COMPREHENSIVE DOCUMENTATION AND CRITICS ON TRINAPANCHAMULA (AYUSHDHARA, 2020)
The word Panchamula is composed of two words Pancha (five) and Mula (roots). Trinapanchmula are the effective herbal formulation for Mutravaha Srotogata Vikara. This combination of drugs having Kusha, Kasha, Nala, Darbha, Kandekshu, these are explained separately as Trinapanchamula. In classics there is a sprinkled reference about utility of Trinapanchamula. Generally they are having the properties of Madhura, Kashaya rasa, Snigdha Laghu Guna, Madhura Vipaka, Sheeta Virya and Tridoshahara property. These drugs acts as Jeevaniya, Rasayana, Mutrala, Agnidipana, Ruchi-vardhaka, Garbhasthapaka, Shukra and Rakta Shodhaka, Stanyajanana and useful in Prameha, Daha, Jvara, Trishna, Arshas, Gulma, Hridroga, Vatarakta, Rakta Pitta etc. But in clinical practice it is insufficient to the mark for the application of same. The common health seeker uses many drugs in the form of grass juice in their routine practice in developed countries in that wheat grass is an excellent source for the latest ingredient. Here an attempt made to understand the usage of drug Trinapanchamoola in clinical practice for the management of different diseased condition. Objectives of the Study: The element study of Trinapanchamoola and its clinical utility in present scenario. Materials and Methods: All relevant data regarding the Trinapanchamula from classical text books, Vedic texts, recent articles, journals, and different websites. Results and Conclusion: Trinapanchamula are the group of drugs has been explained in Ayurvedic classics in different diseased conditions. These used as an ingredients of compound formulations and it is recorded in Samhitas as well as in Sangraha Granthas.